PENGEMBANGAN MODEL "SURVEILANS IBU HAMIL DAN NEONATAL RISIKO TINGGI PADA MASA PANDEMI COVID-19 DENGAN MENGGUNAKAN APLIKASI “TINAMILA” - suhartini, suhartini; Ahmad, Ahmad (Jurnal Medikes (Media Informasi Kesehatan), 2022)
The second goal of SDGs, namely to ensure healthy and encouraging life well-being for every one of everything age in 2030, is to reduce the maternal mortality rate by below 70 per 100,000 KH and reduce the Mortality Rate of Neonatal to 12 per 1000 KH. Profile data Mandala Health Center describes the amount. Dead mothers in 2020 found 1 death mother births, death rates mothers (174.2 per 100,000 births alive ). Amount Infant mortality 1 Infant (1.4 per 1000 births live ) Numbers born died 2 people (2.8 per 1000 live births ). Neonatal deaths are as many as 11 people or around 5.5 per 1000 births. Health center midwife information is known reporting mother and baby pain during this, including during the Covid-19 period in 2020-2021 yet walk well, reports of pregnant women and neonatal risks tall During this reported through report monthly posyandu. The research aims to determine the effect of developing a surveillance model for pregnant women and high-risk newborns during the COVID-19 pandemic by using the "TINA MILA" application to increase the competence of cadres and midwives at the Mandala Health Center in 2022/2023. The research methodology uses a quasi-experimental quantitative design using the dependent T-test. The research team tried to develop a reporting model, "surveillance for early detection of high-risk pregnant and neonatal women during the COVID-19 pandemic," using the "TINA MILA" application. The study results show the average distribution of cadres' knowledge values before and after the Model Development training "Surveillance of high-risk pregnant and neonatal women during the Covid-19 pandemic towards increasing the competence of cadres and midwives in the working area of the Mandala Health Center in 2022. The study's results showed a difference in the average score before and after the training, as indicated by the acquisition of the cadre's knowledge value which had increased after the training. The results of the Wilcoxon Non-Parametric statistical test obtained a value of p = 0.000 which means that statistically, it shows that there is a difference in the average value knowledge of cadres about early detection of high-risk pregnant and neonatal women during the covid-19 period by using the TINAMILA application before after training. To facilitate the use of the application and understanding of early detection of pregnant women and high-risk neonates, it needs to be supported by a guidebook for the use of Surveillance for early detection of pregnant women and high-risk neonates using the TINAMILA application.